XPC Protein Improves Lung Adenocarcinoma Prognosis by Inhibiting Lung Cancer Cell Stemness - Wang, Weiyu; Ma, Shengyao; Ding, Zhenyu; Yang, Yang; Wang, Huaijie; Yang, Kunning; Cai, Xiaoshan; Li, Hanyue; Gao, Zhiqin; Qu, Meihua (Frontiers in Pharmacology, 2021)
Objective: Xeroderma Pigmentosum Complementation Group C (XPC) is a protein involving in nucleotide excision repair (NER). XPC also plays an important role in the lung cancer occurrence with the mechanism remian unclear up to date. Studies showed that the increased stemness of lung cancer cells is related to the recurrence and metastasis of lung cancer. This study aimed to study and analyze the correlation of XPC with lung cancer stem cell biomarkers expression and the overall survival (OS) of lung adenocarcinoma patients. Methods: 140 cases of clinical lung adenocarcinoma tissue samples and 48 cases of paired paracancerous tissue samples were made into tissue microarray. Immunohistochemistry (IHC) was used to detect the expression of XPC and CD133 in cancer and paracancerous tissues. Semi-quantitative analysis and statistics were performed by Pannoramic Digital Slide Scanner. The expression of XPC and CD133 in fresh tissues was verified by Western blotting assay. siXPC was used to knock down XPC in lung cancer cell lines to study the effect of XPC on the expression of lung cancer stem cell biomarkers and the ability of cell invasion. And shXPC was used to knockdown XPC in A549 and H1650 to study the effect of XPC on the expression of lung cancer stem cell biomarkers. Results: IHC and Western blotting results showed that XPC expression significantly decreased, while CD133 expression significantly increased in cancer tissues comparing to paracancerous tissues (PXPC<0.0001, PCD133=0.0395). The high level of XPC in cancer was associated with a better prognosis (Log-rank P=0.0577) in lung adenocarcinoma patients. Downregulation of XPC in lung cancer cells showed increased expression of cancer stem cell biomarkers and the increased cell invasion abilities. Conclusion: It is suggested that XPC can exert the ability of anti-tumor formation, tumor invasion and metastasis inhibition, and prognostic survival improvement in lung adenocarcinoma patients by regulating the stemness of lung cancer cells.